Effect of Workforce Agility on Competitive Advantage in Jordan Telecom Companies - Mohammad, Anber Abraheem Shlash; Mohammad, Suleiman Ibrahim Shelash; Al- Daoud, Khaleel Ibrahim; Al Oraini, Badrea; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (Journal of Posthumanism, 2025)
This study aims to investigate the effect of Workforce Agility on Competitive Advantage. The study population comprised top managers who participated in strategy formulation at Jordan telecom companies. A target sampling method was used in this research after assessing the opinions of experts and academic professors who specialize in the strategic field regarding the instrument used to collect data. Initially, the recovered questionnaires were 223 out of 250 distributed, where it was found that 213 questionnaires were usable for statistical analysis, representing a response rate of 85.20%. A structural equation modeling (SEM) method was used to examine the hypothetical impact between the significant research constructs of workforce agility and competitive advantage and the impact of the dimensions of workforce agility on competitive advantage. The outcomes of the hypothesis concerning the workforce agility dimensions (namely adaptability, problem-solving creativity, professional flexibility, ability to cope with work pressures, and acquisition of work skills) in relation to the strategic agility of telecommunications companies show the significance of all these dimensions as indicated by the regression test. A set of recommendations were set based on the study results.